A novel electrode array for resistivity imaging to assess groundwater resource: field test. Issue 4 (7th August 2020) - Ullah, Saif; Zhou, Bing; Iqbal, Muhammad Asim
Abstract : A novel electrode configuration, called enhanced gradient (EGD) array, for two-dimensional (2D) electrical resistivity tomography (ERT) is introduced. The sensitivity, resolution and penetration depth of some popular traditional electrode arrays are compared with those of the new proposed array. Three synthetic geological models – namely, blocks, faults and fold – were used to check the efficiency of the new electrical resistivity survey for subsurface imaging. The proposed EGD array with two most popular arrays (Schlumberger and gradient) was employed to image the artificial aquifer in Liwa area, Abu Dhabi, UAE. The 2D ERT inversion results showed that the new electrode array yields much better images than the Schlumberger and gradient arrays for imaging the synthetic models and real artificial aquifer in the Liwa area of UAE. The new EGD array has advantages over the popular gradient array in terms of pseudo-section coverage and imaging resolution. The novel EGD array can be employed for 2D ERT subsurface mapping application, particularly in groundwater imaging and monitoring surveys.